The media treatment of the Guinean crisis of 2007 - (:unkn) unknown (My University, 2014)
As in many African countries, the Republic of Guinea experienced a major political and social crisis in 2007, a crisis that has caused many casualties. In January 2007, thousands of Guineans took to the streets to denounce the increasing deterioration of the economic and social situation of the country and the repeated interference of President Lansana Conté in court cases. Our research topic focused on the treatment of this crisis by the Guinean press. The content analysis method adopted allowed us to analyze the positioning newspapers deal with the crisis, instead devoted to the subject, the view adopted in articles etc. The analysis to draw conclusions on the media coverage of the event, on the orientation of its journalistic treatment and the acquisition of political, ideological and emotional position of journalists and newspapers.
Keywords: African Research